2022
DOI: 10.3390/cancers14235840
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Sialylation in Cancer Metastasis, Immunity, and Therapeutic Opportunity

Abstract: Sialylation is an enzymatic process that covalently attaches sialic acids to glycoproteins and glycolipids and terminates them by creating sialic acid-containing glycans (sialoglycans). Sialoglycans, usually located in the outmost layers of cells, play crucial biological roles, notably in tumor transformation, growth, metastasis, and immune evasion. Thus, a deeper comprehension of sialylation in cancer will help to facilitate the development of innovative cancer therapies. Cancer sialylation-related articles h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 172 publications
0
3
0
Order By: Relevance
“…Several directly measured glycans containing sialic acid, such as H6N5S2F1, H7N6S3, and H6N5S3F1 also demonstrated an increased trend in patients with ovarian cancer compared with healthy controls. It has been reported that hypersialylation could enhance immune evasion and tumor cell survival, and stimulate tumor invasion and migration, 38 , 41 which may contribute to the development and progression of ovarian cancer. Additionally, we have also observed a significant increase in glycans H3N4 and H3N5, as well as the derived trait G0 (measuring all agalactosylated glycans), corresponding to previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Several directly measured glycans containing sialic acid, such as H6N5S2F1, H7N6S3, and H6N5S3F1 also demonstrated an increased trend in patients with ovarian cancer compared with healthy controls. It has been reported that hypersialylation could enhance immune evasion and tumor cell survival, and stimulate tumor invasion and migration, 38 , 41 which may contribute to the development and progression of ovarian cancer. Additionally, we have also observed a significant increase in glycans H3N4 and H3N5, as well as the derived trait G0 (measuring all agalactosylated glycans), corresponding to previous research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, through upregulating sialyltransferases content, oncogenes Ras and c-Myc respectively increased the sialylation levels of β1 integrin and E-selectin ligand, further inducing epithelial-mesenchymal transition (EMT) process in cancer cells 12 , 13 . Additionally, one of the reasons why cancer cells can evade immune surveillance is that the elevated levels of sialic acids located in the outermost layer of cancer cells, sialylation of MHC class I–related chain A, sialylated tumor-associated carbohydrate antigens limit the anti-tumor immune response 14 . These findings provide some valuable insights into the potential role of sialylation-related molecules as biomarkers in clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant salivary acidification was observed in preceding research to play a critical role in the growth, metastasis, and immune evasion of several tumors 5,6 and could be applied as a biomarker for specific tumors. 7 Sialylation is a type of glycosylation that covalently attaches sialic acid to the terminal glycans of glycoproteins and glycolipids to produce sialic acid-containing sialoglycans, 8 which usually covers the surface of tumor cells and can be adopted as tumor-associated antigens serving as biomarkers for the detection and monitoring of cancer, including sialyl-Tn (sTn), sialyl-T (sT) and sialyl-Lewis antigens et al 9 Numerous pieces of evidence have shown that the dense sialoglycans coat on the surface of tumor cells has significant implications in promoting tumor growth, metastasis, and immune evasion. 10,11 Sialylation of integrins and selectins can interfere with cell adhesion molecules and promote the metastasis of neoplasm cells to distant sites, 12,13 alternatively in ovarian cancer sialyltransferase ST3GAL1 (ST3 β-Galactoside α-2,3-Sialyltransferase 1) can also promote tumor metastasis through the TGF-β1 (Transforming growth factor-β1) signaling pathway induces EMT (Epithelial-Mesenchymal Transition) to promote tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%